On the taxonomic status of Lygosoma (Keneuxia) dubium Werner, 1909 - Geissler, Peter; Kupfer, Alexander (Zootaxa, 2019)
The species Lygosoma (Keneuxia) dubium was described by Franz Werner (1909) based on a single specimen from the Royal Natural History Cabinet (Königliches Naturalienkabinett) in Stuttgart, collection number 3651. According to the original description the specimen was collected by “Direktor Mayer” in Yokohama, Japan in 1897. Much later Nakamura & Ueno (1963) transferred the species to the Genus Dasia Gray, 1839, without further comments. Recently Uetz et al. (2018) questioned the type locality given by Werner (1909) and suggested that the name Lygosoma dubium is likely to be a synonym of Dasia grisea (Gray, 1845) referring to a personal comment of T. Hikida in 2014. However the actual taxonomic status of the species still remains unresolved.